2020
DOI: 10.3390/cryst10040287
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric Planar Microcavities Doped with a Europium Complex

Abstract: Organo-metallic europium complex tetrakis (dibenzoyl methide) triethylammonium (EuD4TEA) shows a sharp emission spectrum, which makes it interesting for photonic applications. In this work, we embedded it into all-polymeric planar microcavities and investigated the effect of the photonic environment on its emission spectrum. To this end, submicron-sized EuD4TEA crystals were loaded into a blend of polystyrene and carboxylic terminated polystyrene matrix, which served to stabilize the emitter in the polymer and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 58 publications
0
10
0
3
Order By: Relevance
“…These families of emitters are interesting due to the simplicity of tuning their photoluminescence properties by synthetic routes, the ease of processing, and the high-quality films achievable. Indeed, polymers have often been used also to implement organic molecules and nanocrystalline emitters into cavity layers to achieve emission reshaping, lasing, and modification of the emission properties as they facilitate obtaining structures with optical quality and therefore performance, otherwise hardly achievable. ,,, For this purpose, we fabricated a microcavity inserting a defect layer made of F8BT (see the Experimental Section) in a PMMA/Ti–Hy structure (Figure S14). As discussed in the Supporting Information, the microcavity shows optical behavior in agreement with theoretical predictions proving the full compatibility of the hybrid with both polymer dielectric materials and emitters …”
Section: Resultsmentioning
confidence: 99%
“…These families of emitters are interesting due to the simplicity of tuning their photoluminescence properties by synthetic routes, the ease of processing, and the high-quality films achievable. Indeed, polymers have often been used also to implement organic molecules and nanocrystalline emitters into cavity layers to achieve emission reshaping, lasing, and modification of the emission properties as they facilitate obtaining structures with optical quality and therefore performance, otherwise hardly achievable. ,,, For this purpose, we fabricated a microcavity inserting a defect layer made of F8BT (see the Experimental Section) in a PMMA/Ti–Hy structure (Figure S14). As discussed in the Supporting Information, the microcavity shows optical behavior in agreement with theoretical predictions proving the full compatibility of the hybrid with both polymer dielectric materials and emitters …”
Section: Resultsmentioning
confidence: 99%
“…Contrarily, the spectral overlap between the PBG and the microcavity mode of MC tuned and the emission of the NIR dye completely alters the fluorescence shape and intensity, giving rise to a dramatic spectral redistribution well known in these systems independently of the emitter used. 41,47,48 As expected from the typical LPDOS, the emission from wavelengths that correspond to the PBG are completely suppressed due to the near-zero LPDOS, and the emission is funnelled instead into the wavelengths with higher LPDOS at the cavity mode. Remarkably, due to the relatively wide PBG, approximately all off-resonance PL is suppressed, which was not the case for all-polymer microcavities previously reported.…”
Section: Steady-state Optical Characterisationmentioning
confidence: 78%
“…Remarkably, due to the relatively wide PBG, approximately all off-resonance PL is suppressed, which was not the case for all-polymer microcavities previously reported. 45,[47][48][49] A careful comparison of fluorescence and transmittance of the tuned microcavity is reported in Fig. S5 (ESI †) in order to highlight the overlap of the PL enhanced peak and the cavity mode.…”
Section: Steady-state Optical Characterisationmentioning
confidence: 99%
See 1 more Smart Citation
“…Starting from a 1D photonic crystal prepared by consecutive spin-coated layers of two polymeric materials, Lova et al reported the fluorescence control of an emissive layer, containing a fluorescent europium complex, into an all-polymeric planar microcavities. By placing the europium complex in the defect layer of the PC, a spectral and directional redistribution of emission was obtained due to modified photonic states of the cavity [1].…”
mentioning
confidence: 99%